Nonlinear scanning laser microscopy by third harmonic generation - Barad, Y.; Eisenberg, H.; Horowitz, M.; Silberberg, Y. (Appl. Phys. Lett., 1997)
Third harmonic generation near the focal point of a tightly focused beam is used to probe microscopical structures of transparent samples. It is shown that this method can resolve interfaces and inhomogeneities with axial resolution comparable to the confocal length of the beam. Using 120 fs pulses at 1.5 μm, we were able to resolve interfaces with a resolution of 1.2 μm. Two-dimensional cross-sectional images have also been produced.